Periodic acid–Schiff-positive loops and networks as a prognostic factor in oral mucosal melanoma. Issue 2 (April 2016) - Song, Hao; Jing, Guangping; Wang, Lizhen; Guo, Wei; Ren, Guoxin
Abstract : The prognostic factors of oral mucosal melanoma (OMM), a rare and aggressive neoplasm, remain to be determined. The aim of this study is to investigate the prognostic significance of vasculogenic mimicry in OMM. The clinical data of 62 patients with primary OMM treated in Shanghai Ninth People's Hospital from April 2007 to April 2012 were retrieved and analyzed retrospectively. Staining of periodic acid–Schiff (PAS) and CD31 immunohistochemistry were performed to evaluate the prognostic value of PAS-positive patterns, blood lakes, and microvascular density. PAS-positive loops and networks ( P <0.001) as well as blood lakes ( P =0.040) were found to be predictors of overall survival (OS). The presence of PAS-positive loops and networks was an independent prognostic factor of poor OS in multivariate analysis ( P =0.002). Although the presence of PAS-positive loops and networks was associated with hematogenous metastasis ( P =0.041) and lymphogenous metastasis ( P =0.041), it was not an independent predictor of both types of metastasis in multivariate analysis. Microvascular density was not associated with OS ( P =0.627) and metastasis of OMM patients. PAS-positive loops and networks have a significant prognostic value in OMM. Detection of PAS-positive patterns may lead to better staging and serve as a prognostic parameter of OMM.